超语视角下泉州语言景观特征及其对国际中文教育的启示 - Wenlong Liu; Yiting Liu; Chili Li (Journal of Maobi, 2025)
Guided by translanguaging, this study explores the linguistic landscape in Quanzhou and its implications for international Chinese education. The findings indicate that Quanzhou’s linguistic landscape is dominated by Chinese-English bilingualism, while also featuring a variety of minority languages, reflecting the city’s internationalization and cultural inclusiveness. In terms of presentation forms, purely linguistic modes and language-plus-image modes are roughly balanced, with equivalent design strategies occupying an absolute dominant position, ensuring clear communication of information. Functionally, the linguistic landscape is primarily driven by commercial advertising, while also serving purposes such as direction and public services, as well as cultural dissemination. Through a systematic analysis of these characteristics, this study not only provides a new empirical case for the study of linguistic landscapes in Chinese cities, deepening theoretical understanding, but also transforms abstract linguistic findings into concrete teaching strategies and curriculum suggestions. It offers significant practical insights for international Chinese educators to optimize teaching content and methods, thereby enhancing the practicality and effectiveness of instruction.